2022
DOI: 10.1186/s12885-022-09404-8
|View full text |Cite
|
Sign up to set email alerts
|

MiR-106b-5p regulates esophageal squamous cell carcinoma progression by binding to HPGD

Abstract: Background Several studies have documented the key role of microRNAs (miRNAs) in esophageal squamous cell carcinoma (ESCC). Although the expression of the 15-hydroxyprostaglandin dehydrogenase (HPGD) gene and miR-106b-5p are reportedly linked to cancer progression, their underlying mechanisms in ESCC remain unclear. Methods mRNA and miRNA expression in ESCC tissues and cells were analyzed using RT-qPCR. Luciferase and RNA pull-down assays were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…23 Moreover, these heightened miR-106b-5p levels suppressed HPGD expression, which constituted crucial factors that impact the progression and prognosis of patients with ESCC. 24 Similar to numerous miRNAs, miR-196a-5p significantly contributed as a tumor-associated regulatory factor in various cancers. 25,26 Previous studies have confirmed that miR-196a-5p functioned as an oncogene in ESCC, displaying specific biological behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Moreover, these heightened miR-106b-5p levels suppressed HPGD expression, which constituted crucial factors that impact the progression and prognosis of patients with ESCC. 24 Similar to numerous miRNAs, miR-196a-5p significantly contributed as a tumor-associated regulatory factor in various cancers. 25,26 Previous studies have confirmed that miR-196a-5p functioned as an oncogene in ESCC, displaying specific biological behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐601 could negatively regulating HDAC6, thereby inhibiting ESCC progression 23 . Moreover, these heightened miR‐106b‐5p levels suppressed HPGD expression, which constituted crucial factors that impact the progression and prognosis of patients with ESCC 24 . Similar to numerous miRNAs, miR‐196a‐5p significantly contributed as a tumor‐associated regulatory factor in various cancers 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…The increased expressions of miR-10b-3p, miR-106b-5p, miR-25, miR-320b, miR-602, miR-9, and miR-99b/Let-7e/miR-125a not only show significant correlations with metastasis in ESCC patients, but these miRNAs are also known to increase the invasion, migration, and/or EMT of ESCC cells. Additionally, these miRNAs can promote the metastasis of transplanted tumors, primarily to the lungs[ 52 - 58 ]. Other miRNAs, including miR-1269, miR-17-5p, miR-18a-5p, miR-25-3p, miR-301, miR-373, miR-483-5p, miR-766-3p, and others, display oncogenic roles in metastasis, affecting both ESCC tissues and cells[ 59 - 67 ].…”
Section: The Role Of Mirnas In the Metastasis Of Escc Metastasismentioning
confidence: 99%
“…CRC and other malignancies have been linked to abnormal miRNA expression (Jiang et al 2015). Two miRNAs, miR-20 and miR-21, have been linked to the development and spread of CRC and be dysregulated in this disease (Yang et al 2022, Probst et al 2018.…”
Section: Introductionmentioning
confidence: 99%